2021
DOI: 10.1038/s41388-020-01601-8
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: The long noncoding RNA CRYBG3 induces aneuploidy by interfering with spindle assembly checkpoint via direct binding with Bub3

Abstract: Aneuploidy is a hallmark of genomic instability that leads to tumor initiation, progression, and metastasis. CDC20, Bub1, and Bub3 form the mitosis checkpoint complex (MCC) that binds the anaphase-promoting complex or cyclosome (APC/C), a crucial factor of the spindle assembly checkpoint (SAC), to ensure the bi-directional attachment and proper segregation of all sister chromosomes. However, just how MCC is regulated to ensure normal mitosis during cellular division remains unclear. In the present study, we de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 51 publications
(62 reference statements)
0
18
0
Order By: Relevance
“…Our results were consistent with those of Ren et al and would reveal the potential mechanism underlying the high expression of MMPs, that is, the high expression of ETS-1 in astrocytoma tissue may eventually participate in the high expression of MMPs. The highly aggressive characteristics of malignant tumor cells are closely related to disease progression; the main mechanism of this process is that malignant tumor cells destroy ECM through MMPs and so on to reshape the basic structure of tissues, thereby promoting both the growth of tumor cells and their transfer to other locations (44)(45)(46)(47)(48). As a transcription factor, ETS-1 can mediate the transcription of MMPs, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results were consistent with those of Ren et al and would reveal the potential mechanism underlying the high expression of MMPs, that is, the high expression of ETS-1 in astrocytoma tissue may eventually participate in the high expression of MMPs. The highly aggressive characteristics of malignant tumor cells are closely related to disease progression; the main mechanism of this process is that malignant tumor cells destroy ECM through MMPs and so on to reshape the basic structure of tissues, thereby promoting both the growth of tumor cells and their transfer to other locations (44)(45)(46)(47)(48). As a transcription factor, ETS-1 can mediate the transcription of MMPs, etc.…”
Section: Discussionmentioning
confidence: 99%
“…U87 or the U251 cells were cultured and transfected with vectors according to the manufacturer’s instruction (the Vigene Corporation, Jinan City, Shandong Province, China). Then, the cells were harvested and cell suspensions were injected subcutaneously (near the veins located in the groin on the inside of the lower extremities) into the nude mice ( 44 ). At the injection, mice were reared for 4–8 weeks; then, the mice were sacrificed and tumor tissues were collected for calculation of tumor volumes and weights.…”
Section: Methodsmentioning
confidence: 99%
“…In an non‐small cell lung cancer (NSCLC) study, Guo et al (2021) found that the overexpression of lnc CRYBG3 RNA inhibited the interaction between Cdc20 and Bub3, which activated the APC/C complex prematurely, causing aneuploidy and accelerated development of NSCLC. Long noncoding RNAs are operationally defined as RNA transcripts of >200 nt length that have limited protein‐coding potential (Pei et al, 2018).…”
Section: Bub3 Overviewmentioning
confidence: 99%
“…Lung cancer is a malignant tumor with high mortality. NSCLC is the most common type of lung cancers in human and has one of the highest mortality and morbidity rates in China (Bray et al, 2018) and the rest of the world (Guo et al, 2021; Siegel et al, 2013). In lung cancer with chromosomal instability, mitotic checkpoint dysfunction is often found.…”
Section: Oral Cancermentioning
confidence: 99%
“…Crystallin Beta-Gamma Domain Containing 3 (CRYBG3) is a another upregulated lncRNA resulting in genomic instability in A549 lung cancer cells. The overexpressed of CRYBG3 has been shown to interfere with spindle assembly checkpoint activities through inhibiting the interaction between Bub3 and CDC20, resulting in mitotic catastrophes and the formation of aneuploidy; this can eventually promote tumorigenesis and metastasis in NSCLC (81).…”
Section: Lncrnas In Lung Cancer Genome Instabilitymentioning
confidence: 99%